Gingival Depigmentation With Scraping Technique And Frenectomy With Parallel Technique One Visit Veneer Prep Nursing - Adiguna Putra Walianto; Osa Amila Hafiyyah (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Smile design requires harmony between the teeth and the surrounding soft tissue. In the case of anterior veneer treatment preparation, in patient with midline diastema and hyperpigmentation of gingiva should be adequately assessed. One visit treatment for periodontal surgeries is more beneficial for the patients and operator. In this case report, we reported a single visit treatment of frenectomy and gingival depigmentation to achieve more aesthetically acceptable patient prior to veneer procedure. Case: A 28-year-old female patient came to the Periodontics clinic on referral from the Prosthodontics clinic with chief complaint of gapped upper front teeth and brownish upper front tooth gums. Superior labial frenulum attachment was located on the interdental papilla which extended palatally, causing a central diastema and interfering with the veneer plan. Case Treatment: Gingival depigmentation by scraping technique using scalpel no. 15C and frenectomy by parallel technique using scalpel no. 11 to make two parallel incisions on the lateral side of the frenulum in one visit. Discussions: Periodontal surgery cases that can be performed simultaneously are those in the same region with the advantage that is effectiveness of time and trauma incurred as well as cost efficiency. Dark uneven gingiva can be treated with gingival depigmentation and frenectomy is a procedure that removes the frenulum completely including its attachment to the bone. Conclusion and Suggestions: Gingival depigmentation with scraping technique and frenectomy with parallel technique provide good treatment results and can be performed together in a single visit to address patients' aesthetic demands regarding gingival pigmentation and support central diastema correction through veneer treatment in collaboration with prosthodontics.